2019
DOI: 10.1002/mabi.201800384
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Efficacy of Antimicrobial and Antifouling Materials for Urinary Tract Medical Devices: Challenges and Recommendations

Abstract: Device-Associated Urinary Tract InfectionsUrological devices are divided into several different market segments managing, for example, urinary incontinence, urinary stones, treatment of prostate hyperplasia or cancer, and erectile dysfunction. Devices aimed to manage urinary incontinence or maintain the ureter or urethra open and unobstructed, include ureteral stents for the upper urinary tract, urethral stents for the lower urinary tract, and urinary catheters. The focus of this paper is on catheter-and urete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 212 publications
(179 reference statements)
0
88
0
Order By: Relevance
“…Therefore, designing the surface with excellent antibiofouling and self‐healing functions is significant for engineering and biomedicine applications. In the past years, there are some excellent review reports on the antibiofouling included the antibiofouling materials, antibiofouling mechanism, and the antibiofouling design principles . Herein, we mainly focus on the mechanisms of the surface with antibiofouling and self‐healing abilities at interface, particularly the mechanisms up to molecular level and it is anticipated that the description on several typical examples can provide the general design methods for antibiofouling and self‐healing surface.…”
Section: Self‐healing Functional Surfacementioning
confidence: 99%
“…Therefore, designing the surface with excellent antibiofouling and self‐healing functions is significant for engineering and biomedicine applications. In the past years, there are some excellent review reports on the antibiofouling included the antibiofouling materials, antibiofouling mechanism, and the antibiofouling design principles . Herein, we mainly focus on the mechanisms of the surface with antibiofouling and self‐healing abilities at interface, particularly the mechanisms up to molecular level and it is anticipated that the description on several typical examples can provide the general design methods for antibiofouling and self‐healing surface.…”
Section: Self‐healing Functional Surfacementioning
confidence: 99%
“…A flow rate of 2 mL s −1 was used, which yields a shear rate of 15 s −1 and a shear stress of 0.01 Pa [68]. This shear rate is typical for urinary catheters [81] and stents [82], where E. coli is one of the most relevant microbial colonizers [45]. The equipment was also coupled to a water bath to keep a constant temperature of 37 • C. For each sample, the medium with E. coli was allowed to flow for 30 min, after which the coatings were removed and stained with 4 -6-diamidino-2-phenylindole for later visualization under fluorescence microscopy (Nikon Eclipse LV100 series, magnification 100×, Nikon Corporation, Tokyo, Japan) and total cell counts.…”
Section: E Coli Adhesion Assaysmentioning
confidence: 99%
“…Therefore, a deeper investigation of the interactions between bacterial cells and CNT-polymer composites at the interface level could provide insights into the use of CNT-based coatings in medical implants. Testing of these new composites should be performed in hydrodynamic conditions that are relevant for their final application [44] as flow affects the transport of bacteria to the surface and also the forces that adhered cells have to withstand [45]. Additionally, it has been shown that initial adhesion can provide very useful information regarding the antifouling performance of a surface or a coating [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…The fixed cells were stained using the Live/Dead Backlight viability kit with following the manufacturer's protocol. Samples were examined with Leica DMI8 laser scanning confocal microscope (15,16).…”
Section: Assessment Of Biofilm Formationmentioning
confidence: 99%